Ti4O7/g-C3N4 for Visible Light Photocatalytic Oxidation of Hypophosphite: Effect of Mass Ratio of Ti4O7/g-C3N4 - Guan, Wei; Zhang, Zhenghua; Tian, Shichao; Du, Jianwei (Frontiers in Chemistry, 2018)
Hypophosphite wastewater treatment is still a critical issue in metallurgical processes and the oxidation of hypophosphite to phosphate followed by the precipitation of phosphate is an important strategy for hypophosphite wastewater treatment. Herein, Ti4O7/g-C3N4 photocatalysts with various mass ratios (Ti4O7 (m): g-C3N4 (m) = 0.5, 0.2, 0.1, and 0.05) were synthesized by a hydrolysis method and the effect of the mass ratio of Ti4O7 (m): g-C3N4 (m) on Ti4O7/g-C3N4 visible light photocatalytic oxidation of hypophosphite was evaluated. The as-prepared Ti4O7/g-C3N4 were characterized and confirmed by SEM, XPS, XRD and FTIR. Moreover, the specific surface area and the distribution of pore size of Ti4O7/g-C3N4 was also analyzed. Our results showed that Ti4O7/g-C3N4 exhibited remarkably improved photocatalytic performance on hypophosphite oxidation compared with g-C3N4 and meanwhile 1:2-Ti4O7/g-C3N4 with a mass ratio of 0.5 showed the best photocatalytic performance with the highest oxidation rate constant (17.7-fold and 91.0-fold higher than that of pure g-C3N4 and Ti4O7, respectively). The enhanced performance of photocatalytic oxidation of hypophosphite was ascribed to the heterojunction structure of Ti4O7/g-C3N4 with broader light absorption and significantly enhanced efficiency of the charge carrier (e−-h+) generation and separation. Additionally, the generated ·OH and ·O2- radicals contributed to the hypophosphite oxidation during the photocatalytic system.